POPULATION DYNAMIC OF ENDEAVOUR SHRIMP (Metapenaeus elegans) IN THE WATERS OF SOUTH COAST OF JAVA - Ali Suman; Budi Iskandar Prisantoso; Gatut Bintoro (Indonesian Fisheries Research Journal, 2007)
Study on the population dynamic of endeavour shrimp (M. etegans) was conducted in the south coast of Java baied on data collected during a period of November 2002to october 2003. The purpose of the study is to identify biological and population parameters of the endeavour shrimp.